Analysis of Security Threats of Cloud Computing - Svoboda, Tomas; Karamazov, Simeon (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
The aim of this paper is to introduce the result of a long-term research done in the Czech Republic and focused on the security of cloud services. The results of the research reflect more than eighty representatives of national and supranational organizations in the environment of the Czech Republic, and also state organizations within self-government territorial units. The paper examined cloud deployment issues connected with the current legislative and law on cybernetic security. The results of the research are summarized in a SWOT analysis.